2017
DOI: 10.1002/chem.201700960
|View full text |Cite
|
Sign up to set email alerts
|

Photolysis of a High‐Spin Azidoiron(III) Complex Studied by Time‐Resolved Fourier‐Transform Infrared Spectroscopy

Abstract: The laser-flash photolysis of the high-spin azidoiron(III) complex [Fe (Me Cyclam-ac)(N )]PF ([1]PF ) in liquid acetonitrile solution at room temperature was explored by time-resolved Fourier-transform infrared spectroscopy. Excitation of [1] at 480 and 266 nm induced a photoreduction of the metal center and generated [Fe (Me Cyclam-ac)(NCCH )] ([2]) and azidyl radicals. Both photoproducts were detected independently through scavenging experiments. The metal-containing fragment was quenched with carbon monoxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…Initially, most iron nitrides were successfully prepared in frozen solutions, which indicated that a solid matrix and low temperatures were required for their generation . However, ultrafast experiments have recently shown the formation of iron nitrides at room temperature …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Initially, most iron nitrides were successfully prepared in frozen solutions, which indicated that a solid matrix and low temperatures were required for their generation . However, ultrafast experiments have recently shown the formation of iron nitrides at room temperature …”
Section: Figurementioning
confidence: 99%
“…[19,20] However,u ltrafast experiments have recently shown the formation of iron nitrides at room temperature. [21][22][23] Herein, we report the photodissociation of iron(III) azides studied at the molecular level by ion spectroscopy using different temperatures (3-310 K). [24][25][26][27] Photo-dissociation of mass-selected iron azide complexes 1 [28] in the visible range resulted in photoreduction associated with N 3 C elimination or photooxidation, forming the desired iron-(V) nitride complex 3,concomitantly with the elimination of N 2 (Scheme 1).…”
mentioning
confidence: 99%
“…Whereas the ensuing chemical processes of such nascent products are understood quite straightforwardly in terms of first-order, pseudo-first-order, or second-order kinetics depending on the molecularity and the reaction conditions, , the primary elementary steps are often more difficult to quantify. This is because such processes generally occur on very short time scales (from a few tens of femtoseconds to hundreds of picoseconds), and their experimental observation necessitates sophisticated ultrafast laser spectroscopies.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently undertaken a significant research effort aimed at unraveling the photochemical and photophysical primary processes leading to the formation of high-valent nitridoiron­(V) species and to study in detail their chemical reactivities in liquid solution under ambient conditions using a combination of ultrafast mid-infrared (MIR) spectroscopy and time-resolved Fourier-transform infrared (FTIR) spectroscopy following flash photolysis. It was found that the desired dinitrogen cleavage and photooxidation of the iron center has to compete with the heterolytic cleavage of azide anions on the one hand and the homolytic loss of azide radicals and photoreduction of the metal on the other. An increase of the photolysis photon energy leads to a rising quantum yield for photooxidation.…”
Section: Introductionmentioning
confidence: 99%